Sloshing of liquid in tank / Mohd Nazri Omar - Omar, Mohd Nazri (2005)
The subject of sloshing of liquid in a tank has been discussed frequently in the last five years, due to its significance to the carriers of the liquid such as oceangoing vessels and airplanes. The interaction between water and air in closed rectangular tank is studied. Analysis of the case has been conducted using PHOENICS as the CFD software. The author has collaborated closely with the thesis of Mahamad Hisyam Mahamad Basri [1], for the sake of validation requirement. Few problems have been encountered, which mostly are related to the geometrical development and the simulation results. Remedies and recommendations in refining the case results are discussed and concluded, within various perspectives.